Effect of short-term positive airway pressure on blood pressure in controlled hypertensive patients with obstructive sleep apnoea syndrome: a prospective cohort study. Issue 1085 (30th December 2015) - de Morais Lima, José Heriston; da Cruz Santos, Amilton; Barros, Sandra Emília Benício; Soares de Abreu Morais, Pollyana; Figueiroa, José Natal; Alves, João Guilherme B
Abstract: Background: Obstructive sleep apnoea syndrome (OSAS) is associated with cardiovascular disease, especially in patients with high blood pressure. Continuous positive airway pressure (CPAP) seems to contribute to blood pressure control in patients with OSAS, mainly those with uncontrolled hypertension. However, the effect of CPAP on controlled hypertensive patients with OSAS is not known. Objective: To evaluate the effects of CPAP on blood pressure of controlled hypertensive patients with OSAS. Design: Prospective cohort study. Patients: 36 recently diagnosed patients with OSAS and hypertension controlled with oral antihypertensive medication. Methods: CPAP was performed for 5 days. Systolic and diastolic blood pressure were recorded at baseline and 5 days later using 24 h ambulatory blood pressure measurement. Results: Mean (SD) 24 h systolic blood pressure was reduced from 128.9 (3.4) to 126.5 (3.5), p<0.001 and mean (SD) 24 h diastolic blood pressure was reduced from 86.9 (3.3) to 84.8 (3.3), p<0.001. A reduction in the proportion of 'non-dippers' in the participants was registered (from 40.6% at baseline to 18.2%). Conclusions: A short course of CPAP may reduce systolic and diastolic blood pressure in patients with OSAS and controlled hypertension. Trial registration number: RBR – 386qsg; Brazilian Clinical Trials Registry (REBEC).